Living the 7 habits - "Covey,Stephen R." (London, 2000)
In the ten years since its publication, The 7 Habits of Highly Effective People has become a worldwide phenomenon, with more than twelve million readers in thirty-two languages. Now, Living the 7 Habits demonstrates how to solve problems and overcome challenges by applying Covey's proven principles. In this uplifting and riveting collection of true stories, readers will find hope and encouragement as they learn firsthand ways in which the 7 Habits can bring about tremendous, positive change. Enhanced with the personal commentary and insights of Dr. Stephen R. Covey, these touching and motivating stories will inspire readers with an energizing recognition of their own freedom, potential, and power.
Keywords: Psychology